Legitimasi dan Kepastian Hukum Sertifikat Elektronik: Transformasi Digital Sistem Pertanahan Indonesia - Sukarno, Karmila Sari (CV. Kurnia Grup, 2025)
The digitalization of land administration through the implementation of electronic land certificates constitutes an integral part of public service modernization and bureaucratic reform in the land sector. This policy aims to enhance efficiency, transparency, and legal certainty in land registration, while simultaneously responding to the high incidence of agrarian conflicts in Indonesia. This study employs a library research method by examining statutory regulations, legal doctrines, and relevant literature to analyze the legitimacy and legal certainty of electronic land certificates. The findings indicate that, from a normative perspective, electronic land certificates have obtained legal recognition as electronic documents and valid legal evidence, and provide administrative certainty through electronic systems and electronic signatures. Nevertheless, substantive legal certainty has not been fully ensured, as the foundation of Indonesian land law continues to adhere to a negative publication system and the regulation of electronic land certificates remains at the level of ministerial regulations. Furthermore, the legitimacy of electronic land certificates is strongly influenced by system reliability, data security, and the accuracy of issuance and media conversion procedures. Therefore, strengthening the regulatory framework, enhancing data security and system integration, and implementing more comprehensive verification mechanisms are necessary to ensure legal certainity and gaining broad acceptance within society.